A NEW APPROACH TO THE GOVERNANCE AND SECURITY OF PUBLIC ADMINISTRATION INFORMATION SYSTEMS IN MOROCCO - KOUNAIDI , Houssain; RYAHI, Abdellatif; CHERKAOUI , Mariem; GUEDIRA, Mohamed (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Following the acceleration of the development of digital transformation worldwide, we are now witnessing the rise of vulnerabilities in information systems in several countries. Hence the importance for organizations to adopt new organizational and technological strategies, in order to optimize the risks weighing on information processed in the information systems. As a result, the consideration of risk at the organizational level is the subject of much scientific research. The purpose of this article, is to draw up an inventory of the approach recommended to secure the information assets of public administrations in Morocco based on the analysis of security risks, by taking a practical case study "a large public administration in Morocco "whose name will not be exposed for reasons of security and confidentiality, and also propose recommendations for a successful program of security (IS) effective.